1978
DOI: 10.1113/jphysiol.1978.sp012513
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of ventricular cardiac muscle.

Abstract: SUrMARY1. The load bearing capacity during relaxation of ventricular cardiac muscle from various animal species was investigated.2. The effect of load on the time course of relaxation was analysed either by comparing afterloaded contractions against various loads or by imposing abrupt alterations in load (load clamps).3. In heart muscle from the mammalian species studied relaxation was sensitive to loading conditions, whereas in frog heart muscle relaxation was largely independent of the loading conditions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
3

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 45 publications
4
63
3
Order By: Relevance
“…18 The effect of late systolic load on LV relaxation has also been the subject of previous studies. Brutsaert et al 19 initiated the concept of load-dependence of relaxation and described acceleration of relaxation and early termination of a twitch contraction in response to late systolic load clamps. This, however, was only observed in isolated cardiac muscle with isotonic-isometric relaxation sequence and isometrically contracting hearts subjected to volume clamps.…”
Section: Discussionmentioning
confidence: 99%
“…18 The effect of late systolic load on LV relaxation has also been the subject of previous studies. Brutsaert et al 19 initiated the concept of load-dependence of relaxation and described acceleration of relaxation and early termination of a twitch contraction in response to late systolic load clamps. This, however, was only observed in isolated cardiac muscle with isotonic-isometric relaxation sequence and isometrically contracting hearts subjected to volume clamps.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon plausibly corresponds with a depressed force-length relation in cardiac muscle (18,33). It is interesting to note that Edman and Nilsson (33) found that in cardiac muscle, after constant velocity shortening contraction, force is decreased to an amount related to the shortening velocity.…”
Section: Co T a + Ementioning
confidence: 92%
“…This phenomenon is not accounted for by pure elastance-resistance models. On the cellular (59), as well as on the muscular (16,18,33,73) level, it has long been known that the capability to redevelop force after fiber shortening, is negatively affected. The present study, however, indicates that it is the shortening itself, rather than the state of having shortened that is associated with deactivation.…”
Section: System Identificationmentioning
confidence: 99%
“…In mammalian ventricular muscle, comparative analysis of the time course of a series of afterloaded isotonic contractions against various loads up to full isometric twitch, proved that early deactivation occurred when the muscle was allowed to shorten against a load, resulting in a load-induced premature isometric relaxation (Brutsaert et al, 1978b). Figure 1 shows the length and force traces of an atrial strip that went through a similar course of Results are expressed as mean ± SE.…”
Section: Mammalian Atrial Strips Afterloaded Contractionsmentioning
confidence: 92%